The effect of equipment dead space on multiple breath washout measures - Benseler, Anouk (Respirology, 2015)
BACKGROUND & OBJECTIVE: Multiple Breath Washout (MBW) systems are designed to minimize equipment dead space volume (Vd). Animal and infant studies have demonstrated the impact of increased Vd on MBW measurements. In this study we investigate the effect of Vd of a N(2)MBW system affects MBW measurements in preschool children. METHODS: N(2)MBW measurements were performed in healthy adults under standard conditions; Vd was added to match the relationship between Vd and lung volumes observed in preschool children. Subsequently, subjects were measured on a SF(6)MBW system under standard conditions, and with Vd added to match that of the N(2)MBW system. Healthy preschool children and children with cystic fibrosis were tested on both the N(2)MBW and SF(6)MBW in random order on the same day. A correction equation was derived based on the adult experiments and tested on the preschool data. RESULTS: Increasing the Vd of the N(2)MBW system resulted in a higher Lung Clearance Index (LCI). A strong non-linear relationship between N(2)LCI and the Vd/Vt was observed. When the Vd was equivalent between systems, LCI measured by the SF(6)MBW system was similar to that measured by the N(2)MBW. LCI was higher on the N(2)MBW than the SF(6)MBW in preschool children. Correcting for the equipment Vd of the N(2)MBW resulted in better agreement. CONCLUSIONS: Equipment Vd affects LCI measurements, especially in young children where Vd is large relative to lung volumes.